Use of Batroxobin in Central and Peripheral Ischemic Vascular Diseases: A Systematic Review - Lan, Duo; Song, Siying; Liu, Yunhuan; Jiao, Baolian; Meng, Ran (Frontiers in Neurology, 2021)
Background and Purpose: The mechanism of action of Batroxobin included the decomposition of the fibrinogen to fibrin degradation products (FDPs) and D-dimer and mobilization of endothelial cells to release endogenous nt-PA and to promote thrombolysis. This review aims to summarize current study findings about batroxobin on correcting cerebral arterial, venous, and peripheral vascular diseases, to explore the mechanism of batroxobin on anti-thrombosis process. Methods: A thorough literature search was conducted utilizing the PubMed Central (PMC) and EMBASE databases to identify studies up to June 2021. Data from clinical studies and animal experiments about batroxobin were extracted, integrated and analyzed based on Cochrane handbook for systematic reviews of interventions approach and the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P), including the condition of subjects, the usage and dosage, research observation index and main findings. Results: A total of 62 studies were enrolled in this systematic review, including 26 clinical studies and 36 animal experiments. The 26 clinical studies involved 873 patients with arterial ischemic events, 92 cases with cerebral venous thrombosis, 13 cases with cerebral cortical vein thrombosis, and 1049 cases with peripheral vascular diseases. These patients included 452 males and 392 females aged 65.6 ± 5.53 years. The results revealed that batroxobin had broad effects, including improving clinical prognosis (n=12), preventing thrombosis (n=7), promoting thrombolysis (n=6), and improving vascular cognitive dysfunction (n=1). The effects of batroxobin on reducing neuronal apoptosis (n=8)，relieving cellular edema (n=4), improving spatial memory (n=3), and promoting thrombolysis (n=13) were concluded in animal experiments. The predominant mechanisms explored in animal experiments involved promoting depolymerization of fibrinogen polymers (n=6), regulating the expression of related molecules (n=9); such as intercellular adhesion molecule, heat shock proteins, tumor necrosis factor), reducing oxidative stress (n=5), and reducing inflammation response (n=4). Conclusions: Batroxobin can correct both arterial and venous ischemic diseases by promoting depolymerization of fibrinogen polymers, regulating the expression of related molecules, reducing oxidative stress, and reducing the inflammation response.